"Pedras perigosas e pedras preciosas": antropologia da radioatividade em Lajes Pintadas-RN - Brito, Eduardo Neves Rocha de (2021)
Anthropological studies of the effects of radioactivity have as their object environmental accidents and catastrophes related to the mining activity and the processing of chemical products, with emphasis on the resulting health problems, without taking into account the knowledge of those affected about minerals. This work proposes to highlight the representations about the natural world and the local uses of precious minerals that are dangerous to human health. It proposes a discussion of the implications of radioactivity in the lives of residents of the city of Lajes Pintadas-RN from an anthropological perspective. I will analyze the relationship between local knowledge and scientific knowledge and show how miners, researchers and journalists produce contrasting discourses about minerals, in particular in relation to their dangerousness. The procedural part is divided into two methodological fronts, document analysis and ethnography. Technical reports, media discourses, reports, laws, research projects, publications in journals and scientific texts are evaluated and compared to the results of the observation. The ethnography, interviews and biographical accounts present the perceptions of miners, community leaders, education and health professionals and other residents about the radioactive effects of minerals and show that there has been a redimensioning of perceptions of dangerous stones and of the precious stones. This way, the scientific activities carried out in the city changed the native classification of diseases and provoked a mobilization of residents who questioned themselves about the risks of mining. Finally, I present the local diversity of uses of stones, agents, knowledge and learning, as well as the care and handling of minerals in daily life, associative and professional environment. The joint apprehension of local knowledge and scientific knowledge shows that there are disagreements regarding the effects of minerals on the health of residents. In short, if in the natural world dangerous stones and precious stones are present in the same places, in the speeches of the residents they are evoked together; this perception contrasts with the results of scientific research on radioactive minerals. This research also highlights the importance of creating public health policies that recognize the perception of residents and treat the population's illnesses as a problem of natural radioactivity.